2021
DOI: 10.3390/ijms22042047
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 and Sirtuin 3 in Granulosa Cell Tumors

Abstract: Sirtuins (SIRTs) are NAD+-dependent deacetylases that regulate proliferation and cell death. In the human ovary, granulosa cells express sirtuin 1 (SIRT1), which has also been detected in human tumors derived from granulosa cells, i.e., granulosa cell tumors (GCTs), and in KGN cells. KGN cells are an established cellular model for the majority of GCTs and were used to explore the role of SIRT1. The SIRT1 activator SRT2104 increased cell proliferation. By contrast, the inhibitor EX527 reduced cell numbers, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
2
12
2
Order By: Relevance
“…Controversial results were reported on SIRT1's impact on GC viability from various species, which will be described below [51][52][53][55][56][57]. In a recent study aimed to reveal the effect of SIRT1 on hGLC viability, SRT2104 was incubated with intact primary hGLCs and SVOG cells or with SIRT1-silenced cells [51,53].…”
Section: Sirt1 Activation and Gc Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversial results were reported on SIRT1's impact on GC viability from various species, which will be described below [51][52][53][55][56][57]. In a recent study aimed to reveal the effect of SIRT1 on hGLC viability, SRT2104 was incubated with intact primary hGLCs and SVOG cells or with SIRT1-silenced cells [51,53].…”
Section: Sirt1 Activation and Gc Healthmentioning
confidence: 99%
“…A number of in vitro studies also suggested that SIRT1 is involved in diverse ovarian functions including ovarian cell proliferation, apoptosis, folliculogenesis, oogenesis, and secretory activity [30,[47][48][49][50][51][52][53][54][55][56][57][58]. This review aims to provide state-of-the-art information on the expression and divergent roles of SIRT1 in GC function.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1.2 × 10 5 cells were cultured in a 6-well plate overnight, as previously described [34]. Transfection was achieved using predesigned 10 nmol/L GR-siRNA (GR, #sc-35505, Santa Cruz Biotechnology, Dallas, TX, USA) or non-template (NT) control siRNA (10 nmol/L) with Lipofectamine RNA iMAX reagent (#13778150; ThermoFisher Scientific, Waltham, MA, USA) diluted in OPTI-MEM (#31985047, Gibco, ThermoFisher Scientific, Waltham, MA, USA), as described in the manufacturer's instructions.…”
Section: Gr Sirna Studiesmentioning
confidence: 99%
“…Sirtuins induce the deacetylation of a range of protein substrates, including histones, but also mediate ADP ribosylation. Furthermore, overexpression of SIRT1, 2, 3, and 7 have been identified in many types of cancer [ 120 , 121 , 122 ]. For example, overexpression of SIRT1 is known to prevent apoptosis by regulating histone deacetylation, promoter methylation, and histone methylation and inhibiting the transcription of tumor suppressor genes.…”
Section: Acetylationmentioning
confidence: 99%